Soluções de equações diferenciais parciais lineares via transformada de Fourier e espaços de Sobolev - Lima, Maressa Alves (2022)
In this work we present a introdution about the partial di erential equations (PDE) and some techniques for their solutions. Among the techniques explored we detach, the Fourier transform that convert partial di erential equations (PDE) in ordinary di erential equations (PDO), and the Sobolev spaces, which allows weaken the notion of derived reaching a larger set of solutions for PDEs.